On collaborative reference and the roles of the interlocutor - Calado Barbosa, Eduarda (2018)
In this work, I explore the idea that collaboration is required for the completion of acts of referring by asserting propositional content. This claim is supported by an empirical framework first proponed by HH Clark and his coauthors in the late 1980s, but currently under development by researchers in areas such as sociology, linguistics and psychology. I intend to show that, in what concerns philosophical investigations focused on speaker reference, we have reason to suppose that speaker reference is also audience-directed, as suggested by Kent Bach in a recent work. Consequently, we need a nonidealized theory of assertions compatible with the empirical observations of how dyadic spontaneous conversations work. For that, I focus on a critique of Stalnaker?s theory of assertion and offer ways to overcome the difficulties it brings up, defending a collaborative view of assertion-making and acts of referring.